Measuring farm progress of plan II veterans taking institutional on-the-farm training - Early, E. J. F., author; Canada, Ralph W., advisor; Heilig, Herb, committee member; Bicknell, John E., committee member; Horlacher, W. R., committee member (Colorado State University. Libraries, 1949)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Veterans -- Education; Employees -- Training of; Agriculture -- Study and teaching